2002
DOI: 10.1099/0022-1317-51-12-1113
|View full text |Cite
|
Sign up to set email alerts
|

Molecular fingerprinting of fusidic acid- and rifampicin-resistant strains of methicillin-resistant Staphylococcus aureus (MRSA) from Malaysian hospitals

Abstract: The emergence and spread of multiresistant methicillin-resistant Staphylococcus aureus (MRSA) strains, especially those resistant to fusidic acid and rifampicin, in Malaysian hospitals is of concern. In this study DNA fingerprinting by PFGE was performed on fusidic acid-and rifampicin-resistant isolates from Malaysian hospitals to determine the genetic relatedness of these isolates and their relationship with the endemic MRSA strains. In all, 32 of 640 MRSA isolates from 9 Malaysian hospitals were resistant to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…They all expressed high-level rifampicin resistance (MIC, Ͼ256 g/ml), which is higher than the rifampicin MIC of Ͼ4 mg/L and Ͼ16 mg/L reported by Norazah et al 14 …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…They all expressed high-level rifampicin resistance (MIC, Ͼ256 g/ml), which is higher than the rifampicin MIC of Ͼ4 mg/L and Ͼ16 mg/L reported by Norazah et al 14 …”
Section: Discussionmentioning
confidence: 66%
“…9,10 Besides vancomycin, rifampicin has been used in combination with other antibiotics to treat MRSA infections because of its excellent tissue penetration and potent antistaphylococcal properties, 1,7,20 and, until recently, the majority of MRSA isolates remained susceptible. 1,7,21 However, recent reports of rifampicin resistance in MRSA from different countries 3,8,14 suggest that rifampicin resistance in MRSA may be increasing.…”
Section: Discussionmentioning
confidence: 95%
“…A report has shown that resistance towards fusidic acid may develop if the drug is used alone (Chambers 1997). In Malaysia, a fusidic acid-rifampicin combination is used as an alternative oral regimen for the treatment of bacteraemia, musculoskeletal and cardiovascular infections caused by MRSA (Norazah et al 2002). Fortunately all of the MSSA used in this study are still susceptible to rifampicin.…”
Section: Isolatesmentioning
confidence: 92%
“…However, literature is having quite a number of reports reporting primary MRSA resistance to rifampin as well as following combination therapy (Yourassowksy et al 1981, Gottlieb et al 1998, Aucken et al 2002, Norazah et al 2002, Srinivasan et al 2006. A study has shown emergence of rifampin resistance to MRSA in tuberculosis wards.…”
Section: Peter F M Choongmentioning
confidence: 99%